TEKNOLOGI DIGITAL UNTUK PEMBERDAYAAN PEDAGANG SAYUR TRADISIONAL [DIGITAL TECHNOLOGY FOR EMPOWERING TRADITIONAL VEGETABLE PEDDLER] - Moechammad Sarosa; Nurafni Eltivia; Putri Elfa Mas’udia; Mochammad Junus; Amalia Eka Rakhmania; Usman Zulhijah Muhamma6 (Universitas Pelita Harapan, 2019)
Rapid growth of online vegetable traders make the traditional one worry about their future, in which the bankruptcy is in near future, like several department store and other conventional businesses. The proposed digital technology is an online business tool for traditional vegetable peddlers aimed at supporting them to compete with online vegetable traders, building a better trading management, and equip them with information technology development and usability. Customer could order vegetables to the peddler through an application. The application will notify peddlers about the corresponding order, thus the peddler could pack and deliver the orders along with that day’s orders to the correct address. Market potential of this apps is highly large, due to the number of potential customers as well as the peddlers. To make it more efficient, this application implement zoning approach, in which customers areas are divided into several zone, differ from its number of population and area size. By implementing this method, the delivery process could be arranged in accordance with the shipping line in each zones, resulted in minimizing our shipping cost. The implementation of this application aimed to secure the peddlers job, protecting them from the unhealthy development and growth of online vegetable traders.